Development Communication Process and Theories: An Overview - Inyang, Mayen-Julia Paul; Alegu, Johnson Chinasa; Maku, Babatunde Stephen (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
This work examines the process involved in development communication and reviews some related theories as propounded by various scholars. The quest for effective means of implementing development programmes and the need to address the challenges of avoidance and rejection by the target recipients prompted the adoption of some communication strategies to create awareness and elicit acceptance to facilitate the development process to attain appreciable success. This approach was successfully applied by some countries before it was adopted by the United Nations Organisation (UNO) after World War II in 1945 to address the devastating effects in the war-ravaged areas and also carry out development programmes across the globe. Though known by various related names, the concept of development communication became more popular in the 1950s and eventually gained recognition as an academic discipline leading to the postulation of various theories with the Participatory theory regarded as the most preferred by developing countries. The proponents of the concept argue that target audience participation in the process of development can be better enhanced by employing effective communication techniques and appropriate channels including mass media broadcasts.